BISEKSUAL SEBAGAI ALASAN PERCERAIAN PERSPEKTIF MAQASHID SYARI’AH (Studi Putusan Pengadilan Agama Balikpapan Nomor: 162/Pdt.G/2023/PA.Bpp) - Fitri, Desi Widya; Azwar, Zainal; Bahar, Muchlis (TAHKIM, 2024)
Bisexuals in Law no. 1974 concerning marriage and KHI cannot be used as the cause of marriage dissolution. However, the Balikpapan Religious Court Number: 162/Pdt.G/2023/PA.Bpp granted the Plaintiff's lawsuit stating that the reason for the lawsuit was sexual disorders. This research aims to analyze the considerations of the Balikpapan Religious Court judge in granting a divorce lawsuit due to sexual disorders and the maqashid sharia view of bisexuals. This research uses the library research method, which is a data collection technique by reviewing various scientific sources, such as: journals, laws and others. The results of this research are first, it is not correct if the main cause of divorce is sexual misconduct. Therefore, PA Balikpapan concluded that the case above which was the main factor in divorce was constant fighting. Although it cannot be denied that the cause of the quarrel is sexual disorders. Second, bisexuals have violated the concept of maqashid sharia in the hifzu al-din section, namely violating the provisions of the Qur'an and sunnah, then bisexuals also violate hifzu an-nafs, namely causing AIDS, and finally violating the concept of hifzu al-nasl. Key Word: bisexuals, religious courts